Effect of hybrid reinforcement and number of passes on microstructure, mechanical and corrosion behavior of WE43 Mg alloy based metal matrix composite. (3rd March 2023) - Maqbool, Annayath; Lone, Nadeem Fayaz; Ahmad, Tariq; Khan, Noor Zaman; Siddiquee, Arshad Noor
Abstract: In this work, a hybrid metal matrix composite with WE43 magnesium alloy as matrix and a hybrid mixture of NiTi, iron, and tin as reinforcement was fabricated using friction stir processing (FSP). The effect of the number of FSP passes on the grain morphology, distribution of reinforced particles, and mechanical properties were evaluated. Scanning electron microscope with energy dispersive spectroscopy was used to study the distribution of reinforced particles, a more uniform distribution was found in the double pass friction stir processed (DP-FSPed) specimen. The grain size was marginally smaller in the DP-FSPed sample compared to the single pass friction stir processed (SP-FSPed) sample. The processed samples showed an increment in hardness values, however, the distribution of hardness values was found uniform in the case of the DP-FSPed specimen, due to better mixing and homogenous distribution of reinforcement particles. The ductility of the DP-FSPed specimen increased by 126 % as compared to the SP-FSPed specimen. The corrosion rate was evaluated using the potentiodynamic polarization test and was found to be higher in the case of the DP-FSPed specimen.